Dinâmica da comunidade microfitoplanctônica relacionada com os parâmetros físico-químicos do estuário do rio Guajará-Mirim (Vigia - PA) - CARDOSO, Fábio Ferreira (Universidade Federal do Pará, 2013)
Estuaries are rich nutrients environments, favoring reproduction and development of several species. Phytoplankton represents a considerable portion of primary production in these environments and, together with other factors, regulates the biological productivity levels. This study aimed to know the microphytoplankton dynamics and its correlation with environmental factors in the Guajará-mirim river’s estuary in the city of Vigia-PA, an important fishery center of the Pará state. Every two months were made collections of the phytoplankton and take measurements of physicochemical parameters in four collection stations along the estuary, in ebb and flood tide periods. Were determined the specific composition and density of microphytoplankton (org.L-1) and analysis of frequency of occurrence, diversity and evenness, clustering and principal components. Seasonally, was noted, mainly during the ebb tide, a considerable physicochemical variation, strongly related with hydrological cycle in the region. Seventy-eight taxa were recorded belonging to the Bacillariophyta (65), Chlorophyta (6), Cyanophyta (3), Dinophyta (3) and Ochrophyta (1) divisions. Bacillariophyta was dominant in species number, frequency of occurrence and density (99.89%). The monthly average densities of the microphytoplankton ranged from 9.999 (July) to 535.411 org L-1 (January). In January happened a bloom of Skeletonema costatum (max = 1.996.613 org.L-1). The microphytoplankton community was characterized as the median diversity (annual general mean = 2.40). The seasonal variation of physicochemical parameters and species density was the predominant factor to the grouping of samples, and it formed two major groups, the first composed by samples of the rainy season and the second by samples of the drought period. The principal components analysis showed that, despite the physicochemical parameters have low spatial and seasonal variability, the variation in rate of rainfall, total dissolved solids content and salinity was decisive in the variation of density of most species and also promoted a slight increase in diversity in the drought period.